2002
DOI: 10.1001/archderm.138.10.1335
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Chronic Erosive Oral Lichen Planus With Low Concentrations of Topical Tacrolimus

Abstract: Background: Chronic erosive oral lichen planus (EOLP) is a severe form of lichen of the buccal mucosa that is often resistant to systemic or topical therapies.Objective: To evaluate the efficacy and safety of topical tacrolimus, 0.1 mg per 100 mL of water, in treating EOLP.Design: Open-label, prospective, noncomparative study, with 6 months of treatment and 6 months of follow-up.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
78
1
7

Year Published

2004
2004
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(88 citation statements)
references
References 19 publications
2
78
1
7
Order By: Relevance
“…However, the chronic nature of the autoimmune mucocutaneous diseases that are often associated with DG might require long-term (6-12 weeks) use of topical tacrolimus, which could be associated with immunosuppressant toxicity, including malignancy. 7,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]35,36 The specific cause (ie, oral lichen planus, pemphigoid) of DG was not determined in the 24 patients in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the chronic nature of the autoimmune mucocutaneous diseases that are often associated with DG might require long-term (6-12 weeks) use of topical tacrolimus, which could be associated with immunosuppressant toxicity, including malignancy. 7,8,[12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28]35,36 The specific cause (ie, oral lichen planus, pemphigoid) of DG was not determined in the 24 patients in this study.…”
Section: Discussionmentioning
confidence: 99%
“…4,6 Topical tacrolimus at concentrations of 0.03%, 0.1%, and 0.3% has been associated with efficacy and tolerability in the treatment of inflammatory skin diseases 12-22 and has been used for oral diseases associated with autoimmune dermatoses. 7,8,[23][24][25] Moreover, studies 19,2° have found that the serum metabolites of tacrolimus were undetectable when the drug was used topically. The drug inhibits the activity of calcineurin, an important intracellular phosphatase and, thereby, T-lymphocyte activation.…”
Section: Introductionmentioning
confidence: 99%
“…L'utilisation de bains de bouche de tacrolimus avec des comprimés de Prograf® a été proposée dans le traitement du lichen plan et montrent une efficacité rapide et importante malgré la faible concentration utilisée par rapport à la celle de la pommade (0,005 mg/mL versus 0,3 à 1 mg/g) [16][17][18]. Les effets secondaires sont mineurs (picotements, irritations) et s'atténuent ou disparaissent habituellement en quelques jours [17].…”
Section: Discussionunclassified
“…11 Several studies have documented this agent efficacy and safety (at a concentration of 0.03% to 0.1%) in the erosive OLP evolution. 13,49,50,51 However, tacrolimus therapeutic levels in OLP patients have been associated with oral absorption after topical application, leading to systemic side effects. 53,54 In addition, OLP relapses after tacrolimus discontinuation are common.…”
Section: Corticosteroids and Other Treatmentsmentioning
confidence: 99%
“…53,54 In addition, OLP relapses after tacrolimus discontinuation are common. 13,50 Pimecrolimus is another calcineurin inhibitor used in OLP treatment. Its action is similar to tacrolimus, but it has no effect on the Langerhans cells.…”
Section: Corticosteroids and Other Treatmentsmentioning
confidence: 99%